Exfoliated black phosphorus gas sensing properties at room temperature. (30th March 2016) - Donarelli, M; Ottaviano, L; Giancaterini, L; Fioravanti, G; Perrozzi, F; Cantalini, C
Abstract: Room temperature gas sensing properties of chemically exfoliated black phosphorus (BP) to oxidizing (NO2, CO2 ) and reducing (NH3, H2, CO) gases in a dry air carrier have been reported. To study the gas sensing properties of BP, chemically exfoliated BP flakes have been drop casted on Si3 N4 substrates provided with Pt comb-type interdigitated electrodes in N2 atmosphere. Scanning electron microscopy and x-ray photoelectron spectroscopy characterizations show respectively the occurrence of a mixed structure, composed of BP coarse aggregates dispersed on BP exfoliated few layer flakes bridging the electrodes, and a clear 2p doublet belonging to BP, which excludes the occurrence of surface oxidation. Room temperature electrical tests in dry air show a p -type response of multilayer BP with measured detection limits of 20 ppb and 10 ppm to NO2 and NH3 respectively. No response to CO and CO2 has been detected, while a slight but steady sensitivity to H2 has been recorded. The reported results confirm, on an experimental basis, what was previously theoretically predicted, demonstrating the promising sensing properties of exfoliated BP.